Framework for Mobile Data Offloading on Clouds - et al., Aradhana (International Journal of Advanced Science and Technology, 2019)
The prime purpose of our research is to achieve an efficient and secure mobile data offloading through a framework that minimizes the computing overhead and transmission latency by establishing a secure communication between cloud environment and mobile using agent manager. In this work we enhance the security in offloaded mobile data using agent to clouds. The proposed framework has many feature: Data Prevention, Threats Detection, Saving Energy and Saving Energy. The framework can perform with remarkable time and energy saving during secure data offloading. We synthesize the results of framework with respect of time and energy generated through benchmarking and statistical modelling to validate performance evaluation results of our framework.